2020
DOI: 10.1016/j.adolescence.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between sleep disturbances and anxiety sensitivity in relation to adolescent anger responses to parent adolescent conflict

Abstract: Introduction: Sleep disturbances are common among adolescents and are associated with elevated anxiety, and dificulties managing affect. Familial conlict is associated with both anxiety sensitivity and adolescent sleep disturbances. No work to date has examined how adolescent sleep disturbances may interact with anxiety sensitivity in relation to adolescent affective responding to parent-adolescent conlict. The current study was designed to address this gap in the literature by examining how adolescent sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…These results were consistent with findings of many previous studies (e.g. Bilsky et al, 2020 ; Brown et al, 2018 ; Lee & Crunk, 2020 ; Lee et al, 2020 ; Samuel et al, 2021 ; Saravanan et al, 2020 ; Satici et al, 2020 ). For instance, Saravanan et al (2020) found that fear and anxiety of covid-19 was strong and positive correlated with psychological distress whereas Babson (2015) confirmed that there were the interactions between sleep disturbance and general fear/anxiety.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results were consistent with findings of many previous studies (e.g. Bilsky et al, 2020 ; Brown et al, 2018 ; Lee & Crunk, 2020 ; Lee et al, 2020 ; Samuel et al, 2021 ; Saravanan et al, 2020 ; Satici et al, 2020 ). For instance, Saravanan et al (2020) found that fear and anxiety of covid-19 was strong and positive correlated with psychological distress whereas Babson (2015) confirmed that there were the interactions between sleep disturbance and general fear/anxiety.…”
Section: Discussionsupporting
confidence: 94%
“…The interrelation between fear, anxiety and sleep disturbances has been confirmed in a number of studies ( Bilsky et al, 2020 ; Brown et al, 2018 ). Sleep disturbances become common and chronic symptoms among youths and correlated with the increase of risks regarding of psychological, somatic and depressive problems ( Bilsky et al, 2020 ).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, it was found that parents with poor economic status and conflicts with their children in adolescence period also have significantly higher anxiety levels. Studies have shown that adolescentparent conflict is associated with anxiety in adolescents (12,17). A study by Bilsky et al (2020) showed that adolescent-parent conflict causes sleep disorders by increasing adolescents' predisposition to anxiety (17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adolescentparent conflict is associated with anxiety in adolescents (12,17). A study by Bilsky et al (2020) showed that adolescent-parent conflict causes sleep disorders by increasing adolescents' predisposition to anxiety (17). Although there are no studies investigating the relationship of conflict with parental anxiety, it is believed that it is inevitable that the increase in anxiety in adolescents will also be observed in parents.…”
Section: Discussionmentioning
confidence: 99%